Ethyl acetate abatement on copper catalysts supported on ceria doped with rare earth oxides - Sónia Alexandra Correia Carabineiro (2016)
Different lanthanide (Ln)-doped cerium oxides (Ce(0.5)Ln(0.5)O(1.75), where Ln: Gd, La, Pr, Nd, Sm) were loaded with Cu (20 wt. %) and used as catalysts for the oxidation of ethyl acetate (EtOAc), a common volatile organic compound (VOC). For comparison, both Cu-free (Ce-Ln) and supported Cu (Cu/Ce-Ln) samples were characterized by N-2 adsorption at -196 degrees C, scanning/transmission electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy and temperature programmed reduction in H-2. The following activity sequence, in terms of EtOAc conversion, was found for bare supports: CeO2 approximate to Ce0.5Pr0.5O1.75 > Ce0.5Sm0.5O1.75 > Ce0.5Gd0.5O1.75 > Ce0.5Nd0.5O1.75 > Ce0.5La0.5O1.75. Cu addition improved the catalytic performance, without affecting the activity order. The best catalytic performance was obtained for Cu/CeO2 and Cu/Ce0.5Pr0.5O1.75 samples, both achieving complete EtOAc conversion below ca. 290 degrees C. A strong correlation was revealed between the catalytic performance and the redox properties of the samples, in terms of reducibility and lattice oxygen availability. No particular correlation between the VOC oxidation performance and textural characteristics was found. The obtained results can be explained in terms of a Mars-van Krevelen type redox mechanism involving the participation of weakly bound (easily reduced) lattice oxygen and its consequent replenishment by gas phase oxygen.